ТHE BEKTASHI ORDER OF DERVISHES IN MACEDONIA DURING SOCIALISM (ЕтноАнтропоЗум, 2020)
The proposed paper aims to offer the reader certain data on the most significant features and specifics of the Bektashi dervish order in Macedonia during the socialist period. Certain political decisions are included, as well as social occurrence and processes that will directly affect on the (non)existence of certain Bektashi tekkes (lodge), but also on the course of bektashi life in general.